Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the quadratic polynomials and verify the relationships between the zeroes and their coefficients, follow these steps:
### Part (i): [tex]\( 8t^2 + 2t - 15 \)[/tex]
1. Finding the Zeroes:
The quadratic equation is given by [tex]\( 8t^2 + 2t - 15 = 0 \)[/tex]. Solving this equation for [tex]\( t \)[/tex], we find the zeroes to be:
[tex]\[ t_1 = -\frac{3}{2}, \quad t_2 = \frac{5}{4} \][/tex]
2. Sum and Product of the Zeroes:
- Sum of the Zeroes:
[tex]\[ t_1 + t_2 = -\frac{3}{2} + \frac{5}{4} = -\frac{6}{4} + \frac{5}{4} = -\frac{1}{4} \][/tex]
- Product of the Zeroes:
[tex]\[ t_1 \cdot t_2 = \left(-\frac{3}{2}\right) \cdot \left(\frac{5}{4}\right) = -\frac{15}{8} \][/tex]
3. Verification with Coefficients:
For a quadratic equation of the form [tex]\( at^2 + bt + c = 0 \)[/tex], the sum of the zeroes is given by [tex]\(-\frac{b}{a}\)[/tex] and the product is given by [tex]\(\frac{c}{a}\)[/tex].
- Sum Relation:
[tex]\[ -\frac{b}{a} = -\frac{2}{8} = -\frac{1}{4} \][/tex]
We see that [tex]\(-\frac{1}{4}\)[/tex] matches the calculated sum.
- Product Relation:
[tex]\[ \frac{c}{a} = \frac{-15}{8} = -\frac{15}{8} \][/tex]
We see that [tex]\(-\frac{15}{8}\)[/tex] matches the calculated product.
### Part (ii): [tex]\( 4\sqrt{3} x^2 + 5x - 2 \sqrt{3} \)[/tex]
1. Finding the Zeroes:
The quadratic equation is given by [tex]\( 4\sqrt{3} x^2 + 5x - 2 \sqrt{3} = 0 \)[/tex]. Solving this equation for [tex]\( x \)[/tex], we find the zeroes to be:
[tex]\[ x_1 = -\frac{2\sqrt{3}}{3}, \quad x_2 = \frac{\sqrt{3}}{4} \][/tex]
2. Sum and Product of the Zeroes:
- Sum of the Zeroes:
[tex]\[ x_1 + x_2 = -\frac{2\sqrt{3}}{3} + \frac{\sqrt{3}}{4} = -\frac{8\sqrt{3}}{12} + \frac{3\sqrt{3}}{12} = -\frac{5\sqrt{3}}{12} \][/tex]
- Product of the Zeroes:
[tex]\[ x_1 \cdot x_2 = \left(-\frac{2\sqrt{3}}{3}\right) \cdot \left(\frac{\sqrt{3}}{4}\right) = -\frac{2 \cdot 3}{12} = -\frac{1}{2} \][/tex]
3. Verification with Coefficients:
For a quadratic equation of the form [tex]\( ax^2 + bx + c = 0 \)[/tex], the sum of the zeroes is given by [tex]\(-\frac{b}{a}\)[/tex] and the product is given by [tex]\(\frac{c}{a}\)[/tex].
- Sum Relation:
[tex]\[ -\frac{b}{a} = -\frac{5}{4\sqrt{3}} = -\frac{5}{4} \cdot \frac{1}{\sqrt{3}} = -\frac{5\sqrt{3}}{12} \][/tex]
We see that [tex]\(-\frac{5\sqrt{3}}{12}\)[/tex] matches the calculated sum.
- Product Relation:
[tex]\[ \frac{c}{a} = \frac{-2\sqrt{3}}{4\sqrt{3}} = -\frac{2\sqrt{3}}{4\sqrt{3}} = -\frac{2}{4} = -\frac{1}{2} \][/tex]
We see that [tex]\(-\frac{1}{2}\)[/tex] matches the calculated product.
Thus, we have found the zeroes of both quadratic polynomials and verified the relations between their zeroes and coefficients.
### Part (i): [tex]\( 8t^2 + 2t - 15 \)[/tex]
1. Finding the Zeroes:
The quadratic equation is given by [tex]\( 8t^2 + 2t - 15 = 0 \)[/tex]. Solving this equation for [tex]\( t \)[/tex], we find the zeroes to be:
[tex]\[ t_1 = -\frac{3}{2}, \quad t_2 = \frac{5}{4} \][/tex]
2. Sum and Product of the Zeroes:
- Sum of the Zeroes:
[tex]\[ t_1 + t_2 = -\frac{3}{2} + \frac{5}{4} = -\frac{6}{4} + \frac{5}{4} = -\frac{1}{4} \][/tex]
- Product of the Zeroes:
[tex]\[ t_1 \cdot t_2 = \left(-\frac{3}{2}\right) \cdot \left(\frac{5}{4}\right) = -\frac{15}{8} \][/tex]
3. Verification with Coefficients:
For a quadratic equation of the form [tex]\( at^2 + bt + c = 0 \)[/tex], the sum of the zeroes is given by [tex]\(-\frac{b}{a}\)[/tex] and the product is given by [tex]\(\frac{c}{a}\)[/tex].
- Sum Relation:
[tex]\[ -\frac{b}{a} = -\frac{2}{8} = -\frac{1}{4} \][/tex]
We see that [tex]\(-\frac{1}{4}\)[/tex] matches the calculated sum.
- Product Relation:
[tex]\[ \frac{c}{a} = \frac{-15}{8} = -\frac{15}{8} \][/tex]
We see that [tex]\(-\frac{15}{8}\)[/tex] matches the calculated product.
### Part (ii): [tex]\( 4\sqrt{3} x^2 + 5x - 2 \sqrt{3} \)[/tex]
1. Finding the Zeroes:
The quadratic equation is given by [tex]\( 4\sqrt{3} x^2 + 5x - 2 \sqrt{3} = 0 \)[/tex]. Solving this equation for [tex]\( x \)[/tex], we find the zeroes to be:
[tex]\[ x_1 = -\frac{2\sqrt{3}}{3}, \quad x_2 = \frac{\sqrt{3}}{4} \][/tex]
2. Sum and Product of the Zeroes:
- Sum of the Zeroes:
[tex]\[ x_1 + x_2 = -\frac{2\sqrt{3}}{3} + \frac{\sqrt{3}}{4} = -\frac{8\sqrt{3}}{12} + \frac{3\sqrt{3}}{12} = -\frac{5\sqrt{3}}{12} \][/tex]
- Product of the Zeroes:
[tex]\[ x_1 \cdot x_2 = \left(-\frac{2\sqrt{3}}{3}\right) \cdot \left(\frac{\sqrt{3}}{4}\right) = -\frac{2 \cdot 3}{12} = -\frac{1}{2} \][/tex]
3. Verification with Coefficients:
For a quadratic equation of the form [tex]\( ax^2 + bx + c = 0 \)[/tex], the sum of the zeroes is given by [tex]\(-\frac{b}{a}\)[/tex] and the product is given by [tex]\(\frac{c}{a}\)[/tex].
- Sum Relation:
[tex]\[ -\frac{b}{a} = -\frac{5}{4\sqrt{3}} = -\frac{5}{4} \cdot \frac{1}{\sqrt{3}} = -\frac{5\sqrt{3}}{12} \][/tex]
We see that [tex]\(-\frac{5\sqrt{3}}{12}\)[/tex] matches the calculated sum.
- Product Relation:
[tex]\[ \frac{c}{a} = \frac{-2\sqrt{3}}{4\sqrt{3}} = -\frac{2\sqrt{3}}{4\sqrt{3}} = -\frac{2}{4} = -\frac{1}{2} \][/tex]
We see that [tex]\(-\frac{1}{2}\)[/tex] matches the calculated product.
Thus, we have found the zeroes of both quadratic polynomials and verified the relations between their zeroes and coefficients.
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.